Kato Katz against Floatation Technique Comparison for Intestinal Helminth Detection of Elementary School Children in Swamp Wetland Area, South Kalimantan, Indonesia - Rifqoh, Rifqoh; Cahyono, Jujuk Anton; Kustiningsih, Yayuk (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2024)
Intestinal helminth infections are the most widespread of the world's neglected tropical diseases, primarily affecting morbidity in school-age children. Early and accurate intestinal helminth detection is important to determine an effective treatment for reducing morbidity. This research objective is to compare intestinal worm infections in elementary school children in swampy wetland areas using the Kato-Katz method and Flotation techniques. Two hundred ninety-six elementary school children in Danau Panggang Swamp-wetland, 6-13 years old, were examined for intestinal helminth eggs in no-preservative feces using microscopies Kato Katz and Floatation. The result of Kato Katz was a total egg counting per gram feces of Ascaris lumbricoides 23-92/gr feces Trichuris trichiura 23-207/gr feces and Fasciolopsis buski 23-69/gr feces, while the results of Floatation only Ascaris lumbricoides 10-50/gr feces Trichuris trichiura 20-90/gr feces. The percentage of intestinal helminth infection by Kato Katz was 31,76% (94 samples), which is higher than by the Floatation was 25,34% (75 samples). The Wilcoxon statistical test obtained a significance value of 0.001, which shows p<α (α=0.05); there is a significant difference between the results of the quantitative examination of intestinal worm eggs between the Kato Katz and Floatation technique. It is recommended that Kato Katz's performance testing be continued compared to PCR methods and a wider sample area.